Parthenolide Induces Apoptosis and Cell Cycle Arrest of Human 5637 Bladder Cancer Cells In Vitro - Cheng, Guang (Molecules, 2011)
Parthenolide, the principal component of sesquiterpene lactones present in medical plants such as feverfew (Tanacetum parthenium), has been reported to have anti-tumor activity. In this study, we evaluated the therapeutic potential of parthenolide against bladder cancer and its mechanism of action. Treatment of bladder cancer cells with parthenolide resulted in a significant decrease in cell viability. Parthenolide induced apoptosis through the modulation of Bcl-2 family proteins and poly (ADP-ribose) polymerase degradation. Treatment with parthenolide led to G1 phase cell cycle arrest in 5637 cells by modulation of cyclin D1 and phosphorylated cyclin-dependent kinase 2. Parthenolide also inhibited the invasive ability of bladder cancer cells. These findings suggest that parthenolide could be a novel therapeutic agent for treatment of bladder cancer.